Pengaruh Current Ratio, Debt to Equity Ratio, Total Aset Turnover terhadap Pertumbuhan Laba pada Perusahaan Subsektor Telekomunikasi yang Terdaftar di BEI - Pamungkas , Oscar; Wiyono, Gendro; Kusumawardhani, Ratih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to examine the effect of current ratio, debt to equity ratio, and total assets turnover on profit growth in telecommunications companies listed on the IDX for the 2018-2021 period. The population in this study is all Telecommunication Companies listed on the IDX. The sampling technique used purposive sampling and obtained samples of 8 companies. The data were processed using classical assumption tests, multiple linear regression, and hypothesis testing using partial tests (t) and determination tests (R2) using the SPSS program 25 The results showed that the current ratio did not affect profit growth, debt to equity ratio did not affect profit growth, total asset turnover did not affect profit growth policy.